The dressmaker ebook - Alcott, Kate (2012)
Tess, an aspiring seamstress, thinks she’s had an incredibly lucky break when she is hired by famous designer Lady Lucile Duff Gordon to be her personal maid on the Titanic.  Once on board, Tess catches the eye of two men—a kind sailor and an enigmatic Chicago businessman—who offer differing views of what lies ahead for her in America. But on the fourth night, disaster strikes, and amidst the chaos, Tess is one of the last people allowed on a lifeboat.     The survivors are rescued and taken to New York, but when rumors begin to circulate about the choices they made, Tess is forced to confront a serious question.  Did Lady Duff Gordon save herself at the expense of others? Torn between loyalty to Lucile and her growing suspicion that the media’s charges might be true, Tess must decide whether to stay quiet and keep her fiery mentor’s good will or face what might be true and forever change her future. BONUS: This ebook edition includes an excerpt from Kate Alcott's The Daring Ladies of Lowell .